Polarization-dependent X-ray absorption spectroscopy of La2CuO4Fx thin films using synchrotron radiation - Chen, J; Nachimuthu, P; Liu, R; Edwards, P (2000)
High-resolution polarization-dependent O K-edge x-ray absorption spectra for c-axis oriented La2CuO4Fx thin films were, investigated. In the O Is absorption edge of La2CuO4FX the prepeak at 528.7 eV is assigned to transitions into O 2pxy hole states located in the CuO2 planes. Fluoride ions present in La2CuO4Fx induce hole states in the CuO2 planes near the Fermi level, which in turn play an important role in enhancing superconductivity for this compound, as compared to parent La2CuO4. In La2CuO4Fx, fluoride ions are regarded as an electronic dopant to induce superconductivity. © 2000 THE PHYSICAL SOCIETY OF THE REPUBLIC OF CHINA.